2021
DOI: 10.1371/journal.pone.0247678
|View full text |Cite|
|
Sign up to set email alerts
|

Transient changes in white matter microstructure during general anesthesia

Abstract: Cognitive dysfunction after surgery under general anesthesia is a well-recognized clinical phenomenon in the elderly. Physiological effects of various anesthetic agents have been studied at length. Very little is known about potential effects of anesthesia on brain structure. In this study we used Diffusion Tensor Imaging to compare the white matter microstructure of healthy control subjects under sevoflurane anesthesia with their awake state. Fractional Anisotropy, a white mater integrity index, transiently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…There is very little data on the impact of sedation on DTI measures. However, at least one study has reported transient changes in DTI measures following sedation in elderly patients ( 80 ). It is impossible to know whether sedation impacted our participants since we did not have a non-sedated baseline scan on them.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little data on the impact of sedation on DTI measures. However, at least one study has reported transient changes in DTI measures following sedation in elderly patients ( 80 ). It is impossible to know whether sedation impacted our participants since we did not have a non-sedated baseline scan on them.…”
Section: Discussionmentioning
confidence: 99%
“…Technical limitations of anisotropic voxels and a single b0 volume in the diffusion MRI acquisition were due to pre-existing scan protocols at our institution, and should be addressed in future studies. The authors acknowledge the limitation of heterogeneous consciousness levels during scanning (older children were more able to tolerate awake imaging than younger children, and infants underwent “feed and wrap” scanning) particularly as anaesthesia may have an effect on dMRI metrics ( Tang et al, 2021 ). Another limitation is the modest sample size for some groups and timepoints (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The study analyses did not consider potential impacts of sedation on imaging metrics. Sevoflurane anesthesia has been shown to result in transient decreases in FA and transient increases in MD ( Tang et al, 2021 ). Further, FA was lower and MD was higher at 100 min than at 40 min post administration of anesthesia.…”
Section: Discussionmentioning
confidence: 99%